Dermoscopy Features of Acquired Perforating Dermatosis Among 39 Patients - Wang, Wenju; Liao, Yansen; Fu, Lixin; Kan, Bei; Peng, Xiaodong; Lu, Yonghong (Frontiers in Medicine, 2021)
In this report, we concluded there are four dermoscopic features of APD including a yellow-brown homogeneous structureless area in the center of the lesion, dotted and linear vessels distribution radially and a dam shape uplift at the periphery, as well as a white irregular ring surrounding the lesion. There are three features, including the yellow-brown homogeneous structureless area in the center of the lesion, the dotted and linear vessels distribution radially and the white irregular ring surrounding the lesion were correspond to the report of Emma Ormerod et al.These features are also similar to those previously discribed in three separated reports of seven cases with APD. In our report, we found a new dermoscopic features: the dam shape uplift at the periphery. These finding may be contributed to improve the rate of clinical diagnosis of APD.